الروح الریاضیة وعلاقتھا بترتیب فرق الكرة الطائرة للنساء - نعيمة زيدان خلف; علاء عبدالرضا عبدالرضا (physical education and sport sciences college for women/ Baghdad University, 2014)
The sport sprit has Ethel value through dealing with competitors and coulees. Although the important of sport sprit specially during the competitions, the researchers have noticed that there isn't assessing tools to evaluate the sides of sport sprit for teams( Previously the researchers were volleyball players and currently they are volleyball coaches in Baghdad girls club for advance women players). Thus, the researchers have adopted sport sprit assessing and introducing its relation on the level of teams. Also, the important of this research lies in the fact that it is the first research caring of sport sprit and its relation of volleyball women teams. The research has concluded the following: 1-The acting of sport sprit assessment for volleyball advance women players. 2- The contributing of the research of limiting the differences of sport sprit level for the volleyball women players of clubs. 3- The contributing of the research of limiting the differences of sport sprit level among the clubs of volleyball women teams. 4- The Finding of corresponded relation between the sport sprit and the level of volleyball women teams. The research has recommended the following: 1-The importance of making lessons and lectures for sport sprit concept for positive behavior and developing the sport sprit., encourage the players of accepting the loss or win, respect the lows and rules of sport system to privet harm and amuse other. 2-The importance of gifting for clean playing and behavior players and adopting punishment for players as well as teams that misbehave of sport sprit. 3-The importance of dealing of sport sprit in psychological and knowledge preparing of teams and transferring them in practical behavior during the